Leisure activities and instrumental activities of daily living: A 3‐year cohort study from the Japan Gerontological Evaluation Study. Issue 2 (22nd December 2021) - Ukawa, Shigekazu; Tamakoshi, Akiko; Tani, Yukako; Sasaki, Yuri; Saito, Junko; Haseda, Maho; Shirai, Kokoro; Kondo, Naoki; Kondo, Katsunori; Kawachi, Ichiro
Abstract : Aim: We prospectively examined the association between leisure activities and changes in instrumental activities of daily living (IADL) among participants of the Japan Gerontological Evaluation Study (JAGES). Methods: We analyzed data collected from 49 732 JAGES participants (23 359 men and 26 373 women), aged ≥65 years, from 24 municipalities in Japan. Measurements: Baseline data were obtained for 25 types of leisure activities in which the cohort members participated. Baseline (2010) and follow‐up (2013) data on IADL were collected – the outcome indicated changes in IADL scores from 2010 to 2013. We regressed changes in IADL scores from the 2010 to 2013 to the number of leisure activities. Results: Older adults who engaged in more leisure activities had higher changes in IADL scores than those who engaged in fewer leisure activities: the β values (95% confidence interval [CI]) of the IADL scores were 0.001 [−0.04–0.04], 0.04 [0.01–0.08], 0.09 [0.05–0.13], 0.09 [0.05–0.14], 0.08 [0.02–0.13], and 0.13 [0.07–0.18] for having one, two, three, four, five, and more than six types of leisure activities ( P for trend <0.001), respectively. Similar associations were found for different types of leisure activities, including predominantly physical and cultural activities. Statistically significant linear trends were obtained among the group, solitary, and other leisure activity subgroups ( P for trend <0.05). Conclusions: Encouraging engagement in leisure activities may promote maintenance of IADL among older populations. Different types of leisure activities appear to have similar positive impacts on IADL. Geriatr Gerontol Int 2022; 22: 152–159 .